Association of skeletal muscle strength and cardiorespiratory fitness with bone mineral density: a cross-sectional study - Wei, Beibei; Miao, Zelong; Yang, Xinge; Chen, Shuning; Guo, Xueying; Wang, Jixiang; Huang, Xu; Zhang, Hanping; Wang, Xuan; Jia, Bin (Frontiers in Public Health, 2025)
BackgroundThe high prevalence and increasing severity of osteoporosis have elevated it to a significant global public-health concern, imposing a substantial economic burden. Skeletal muscle strength and cardiorespiratory endurance serve as pivotal metrics in evaluating physical health. They play a vital role in mitigating the risks associated with bone density decline and the development of osteoporosis. This cross-sectional study was carried out among Chinese adults aged 30–60 years. Its aim is to investigate the associations between skeletal muscle strength, cardiorespiratory endurance, and bone density, thereby providing scientific evidence for formulating prevention and intervention strategies against osteoporosis.MethodA handgrip dynamometer was employed to measure the subjects’ grip strength, which served as an indicator for assessing their upper-limb muscle strength. Additionally, an isokinetic muscle-strength tester was utilized to determine the subjects’ lower–limb isokinetic muscle strength, thereby evaluating the strength of their lower–limb muscles. The exercise cardiopulmonary testing system was utilized to directly measure the subjects’ maximum oxygen uptake (VO₂ max) via a treadmill test. This crucial indicator was then employed to assess the subjects’ cardiorespiratory fitness (CRF). Moreover, the QCT bone density analysis system was used to measure the thoracolumbar bone density of the subjects, and their bone density levels were evaluated based on the T value. A multiple stepwise linear regression model was utilized to further examine the associations between the independent variables grip strength, quadriceps muscle strength, and maximum oxygen uptake and the dependent variable, the bone density T value, stratified by gender. A series of factors potentially influencing the results were adjusted for, such as age, weight, body mass index (BMI), smoking and drinking habits, as well as vitamin D and calcium levels.ResultsIn the final fully adjusted model, a significant positive correlation was detected between grip strength and the BMD T score (β = 0.03, p < 0.001). This correlation held significance in both women (β = 0.15, p < 0.001) and men (β = 0.07, p < 0.001). A significant correlation was observed between quadriceps muscle strength and the bone mineral density T score (β = 0.94, p < 0.001). Notably, this correlation was particularly pronounced in the female group, with a more significant relationship (β = 1.35, p < 0.001), whereas in the male group, the correlation was not significant (β = 0.42, p = 0.230). In addition, a significant correlation was identified between the maximum oxygen uptake and the bone density T value in the overall sample (β = 0.28, p = 0.009). Nevertheless, upon gender stratification, the correlation between the maximum oxygen uptake and bone density was not significant in women (p = 0.884), yet it was significant in men (β = 0.42, p = 0.009).ConclusionIn the 30–60 age group, a significant positive correlation was detected between skeletal muscle strength and bone density. Specifically, in women, lower limb muscle strength was more closely associated with bone density; however, this relationship was not significant in men. Moreover, the association between cardiorespiratory endurance and bone density varied by gender. It was not significant in women but demonstrated a significant positive correlation in the male group.